Building battery physical test for the selection of young football halls for ages ( 14-16 years) - Shafi, Saleh; Ali, Aiya (Journal of Physical Education, 2015)
The research aims to: building a physical test battery for selecting soccer goalkeepers for ages(14-16)years, the researcher used the descriptive survey manner to reach a solution to the problem of research. Research community comprised of (66)soccer goalkeepers for ages(14-16)years and they was as follows(10)goalkeepers to the experiment exploratory (56) goalkeepers to the building and (46)goalkeepers to the standardizing. in order to obtain data ang information on the subject of research, interviews with experts and specialists, quastionnaires and tests and measurement. To find a solution to the problem of research, researcher used statistical means the following: the relative importance, percentage percent, mean, standard deviation, median, coefficient of skewness, simple correlation coefficient (Pearson), T-Test for correlated samples(independent), factor analysis, amended standard degree(the relay way) the data were statistically treated using the statistical pack (SPPS). From the results it has been reached the researched the researcher found: Firstly: factor analysis uing orthogonal rotation, which was conducted on 12 variables representing special tests of physical capacity for soccer goalkeepers and that showed (4) variables were accepted(3) of them in light of the condition for the acceptance factors and factors were accepted are: 1. reaction(first factor) 2. flexibility(second factor) 3. explosive power of the arms(third factor) Secondly: the physical abilities test battery was extracted for soccer goalkeeper for ages (14-16) years in order of its paraments learned which represent the highest saturation on their factors units, and following: 1. nelson test in two directions for reaction. 2. bend the trunk forwarddown from the sitting position test. 3. throwing a medical ball weighing 1 kg test, in one hand from standing to far away as possible. The recommendations are: adoption test battery obtained and used the tests to benefit from them in the selection of soccer goalkeepers for (14-16) years, and make a similar studies in aspects that were not in this study like skills, psychological, functional and physical measurements